ANALISIS OPINI PUBLIK DI TIKTOK TERHADAP KEBIJAKAN PEMBATASAN USIA PENGGUNA MEDIA SOSIAL: STUDI PADA KOLOM KOMENTAR - Hasnawati; Johar Amir; Nurhusna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze public opinion on TikTok regarding the age restriction policy. This study uses a descriptive qualitative approach, with data sources consisting of user comments on TikTok video content discussing the policy. Data were collected through documentation techniques, taking 37 relevant comments. Data analysis was conducted using content analysis, classifying comments into positive, negative, and neutral sentiment categories. The results show that negative sentiment dominated at 48.6%, followed by positive sentiment at 40.5%, and neutral sentiment at 10.8%. These findings indicate that the age restriction policy for social media users continues to generate debate among the public, particularly regarding issues of individual freedom and child protection.